Impact of exercise sequence in concurrent training on insulin resistance, glycemic control, and blood pressure in Type 2 diabetes - Friew Amare; Alemmebrat Kiflu; Aschenaki Taddese (PLoS ONE, 2026)
This study compared the effects of aerobic followed by resistance (CART) and resistance followed by aerobic (CRAT) training on insulin sensitivity, glycemic control, and blood pressure against a non-exercising control group (COT). 39 patients with type 2 diabetes were randomly assigned to CART (n = 13), CRAT (n = 13), or COT (n = 13) for a 12-week supervised program. Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) improved significantly (F = 24.460, p = 0.001, η² = 0.62), with CRAT showing a modestly greater reduction than CART (MD = 0.303, p = 0.022), while both training sequences produced greater improvements compared to COT (CART: MD = −0.493, p = 0.001; CRAT: MD = −0.796, p = 0.001). Fasting Blood Sugar (FBS) decreased significantly (F = 16.206, p = 0.001, η² = 0.519) in both CART (MD = −10.747, p = 0.001) and CRAT (MD = −11.459, p = 0.001) relative to COT, though no difference emerged between the two exercise sequences (MD = 0.712, NS). Systolic Blood Pressure (SBP) also declined in CART (MD = −4.896, p = 0.005) and CRAT (MD = −5.681, p = 0.001) compared with COT (F = 8.968, p = 0.001, η² = 0.374), again without a significant sequence effect (MD = 0.785, NS). No significant between-group changes were observed in Diastolic Blood Pressure (DBP). Overall, concurrent training effectively reduced insulin resistance, improved glycemic control, and lowered SBP in patients with type 2 diabetes. While CRAT offered a modest additional benefit for HOMA-IR, the findings suggest that concurrent training, regardless of sequence, provides meaningful clinical benefits for managing type 2 diabetes. Trial registrationPan African Clinical Trials Registry (PACTR202509591505325) pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=37070